Diagnostic value of sputum cultures in children under 2 years of age with chronic suppurative lung diseases. Issue 12 (12th October 2020) - Stafler, Patrick; Zaks‐Hoffer, Gal; Scheuerman, Oded; Ben‐Zvi, Haim; Mussaffi, Huda; Mei‐Zahav, Meir; Steuer, Guy; Levine, Hagit; Bar‐On, Ophir; Mantin, Hadas; Prais, Dario; Blau, Hannah
Abstract: Background: Acquiring sputum cultures from infants is considered challenging. We describe their yield in infants with cystic fibrosis (CF) and other chronic suppurative lung diseases (CSLDs). Methods: Retrospective medical record review over a 4‐year period, for infants aged 0–2 years with ≥2 airway bacterial cultures acquired by deep suction or induced sputum ≥4 weeks apart. Data included demographics, culture results, and clinical status. Results: A total of 98 infants (16 CF) were evaluated and 534 sputum cultures acquired, 201 in CF and 333 in CSLD. There were 12 (2–23), median (range) cultures/CF infant, and 3 (2–21)/CSLD infant. Age at first culture was 3.8 (1–19.5) months for CF and 10.4 (0.5–22) months for CSLD; p  = .016. In total, 360 cultures (67%) were positive for any bacteria, with 170/234 (73%) positive during exacerbations, compared with 190/300 (63%) during routine visits; p  = .05. More infants with CF than CSLD had cultures positive for Staphylococcus aureus (SA; 75% vs. 34%; p  = .004) throughout the period. Pseudomonas aeruginosa (PA) was common in both CF and CSLD (56% and 44%, respectively; p  = .42) and increased over time for CF but was high throughout for CSLD. The number of hospital days before PA acquisition was 6 (10.2) for CF and 28.8 (38.7) for CSLD ( p  = .003). No CF but 6/82 (7%) CSLD infants had chronic PA ( p  = .56). Conclusions: Sputum cultures showed that infection, in particular PA, is common in CF and CSLD whereas SA is more common in CF. Prospective studies are warranted to elucidate the role of active surveillance in guiding antibiotic therapy.